Radicalism, Visual Culture, and Spectacle in the 1790s - Barrell, John (Romanticism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractThis essay examines the visual propaganda produced by the popular radical movement in the 1790s, chiefly in London. It examines examples of caricatures, especially those by Richard Newton, the token coinage mainly produced by Thomas Spence, the mock play-bills printed by Richard ‘Citizen’ Lee and others, and the portraiture of contemporary radical leaders and heroes published by or on behalf of the movement. It discusses the effectiveness of these as radical propaganda, but its main concern is to ask why the movement seems to have been so little interested in developing a visual culture commensurate with its varied and voluminous literary culture. It looks for the answer chiefly in what it suggests may have been a strong distrust of the visual among popular radicals, and a concern that to exploit the resources of the comic and the grotesque in visual propaganda would have made the movement appear less high-minded, less polite, and easier to despise and dismiss.